The Identity of Theology and Philosophical Proximity: Integration and Divergence Dispute (Journal of Imam Al-Kadhim College, 2023)
ABSTRACTThe paper centres around the nature of the relationship between theology as a science dealing with divine topics and philosophy which represented a culture coming from Greece and had precedence in history in dealing with the most important question of metaphysics-opposing nature-(God). It is also concerned with how Christianity thinkers used the outcome of their predecessors’ knowledge in forming anthology of theology leading to the determination of the identity of this important field by showing interest in reading the proximity between the two, and bringing about the discovery of integration and divergence dispute in formulating the identity of the new field-theology-after relying on knowing the tools leading to the epistemological ends.Thus, the paper aims to determine the nature of identity formation of theology according to a cycle of dispute tagged with caution and mimetism through a group of texts written by great Christian thinkers who constituted the centralization of origins in the formation of Christian thought identity.
Keywords: theology, natural religion, natural theology, Christian philosophy